CARBONIFEROUS CONODONT BIOSTRATIGRAPHY AND LATE PALAEOZOIC DEPOSITIONAL EVOLUTION IN SOUTH CENTRAL IRAN (ASADABAD SECTION - SE ISFAHAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Asadabad section in Central Iran is one of the most complete sequences so far described across the Carboniferous of Iran. The stratigraphic and biostratigraphic data on the sediments overlying the Devonian carbonate platform give evidence about the duration of shallow water depositional evolution. There are thirty productive levels with conodonts in the Carbonifeous section ranging in age from early Tournaisian to the top of Bashkirian (Lower expansa - sulcata to sinuosus zones). There is scarce evidence about the elongatus Zone presence - Late Pennsylvanian. Sulcata to anchoralis-latus conodont zones in Shishtu Formation and muricatus to sinuosus Zone and a possible elongatus Zone in Sardar Formation have been indentified. These conodont zones are reported for the first time in that area. A crinoidal limestone - key bed horizon, is traceable in the studied area as well as in other parts of Iran. It is Early Pennsylvanian-Bashkirian in age and is correlated to sinuatus-minutus Zone. The studied Shishtu and Sardar Formations (Carboniferous) as well as Vazhnan and Surmaq Formation (Permian) in the section belong to marine near shore sedimentation with many macrofaunal remains.
Keywords: Conodonts; Carboniferous; Shishtu Formation; Sardar Formation; Isfahan; Ramsheh area; Asadabad; Iran